Primary School Teachers’ Practice Of Digital Wisdom In The Classroom - Ramdas, Girija (2018)
This research is carried out to explore the practice of digital wisdom among the primary school teachers in the selected schools in Penang. The research instrument for this study was developed using Monika Ardelt’s (2003) theory on wisdom and Heinrich and Molenda’s (1999) ASSURE instructional design model. The instrument consists of six dimensions and 38 items . To ensure its reliability and validity, the instrument was reviewed by two experts in Research and Innovations and an expert in Educational Technology. The instrument also went through pilot study, exploratory factor analysis and Cronbach’s Alpha test to ensure its internal consistency. The instrument was then used in the actual study and data was collected from 372 respondents. The findings show that; i) Most teachers practise digital wisdom in their classroom moderately, ii) Digital status has a significant but weak relationship with the practice of digital wisdom, iii) Age has a significant and moderate relationship with the practice of digital wisdom, iv) There is no significant relationship between the locality and the practice of digital wisdom, v) Gender has no significant relationship with the practice of digital wisdom, vi) There is a significant and moderate relationship between experience and the practice of digital wisdom and vii) Education level of the teachers has no significant relationship with the practice of digital wisdom. The results obtained yields insights on the level of digital wisdom possessed by the teachers and relationships that exist between the practice of digital wisdom and the demographic profiles of the teachers. This study is one of the first few studies related to digital wisdom carried out in Malaysia and it broadens the research scope in the field of instructional technology